htwemia
contestada

1) Solve the system by elimination?

2x-y=-3
5x-4y=6

2) Solve the system by substitution?

3x-y=-1
y=2x-1

Respuesta :

Answer:

1) (-6,-9)

times the top equation buy -4 so you cancel out the y

so it be -8x+4y=12 no cancel out the y's

so it be -8x=12 and 5x=6

now combined like terms to get -3x= 36

x = -6 now go plug that back in one of the equations to get y

y = -9

2) (-2,-5)

now on this one you going to substitute y= (2x-1) for y in the otheir eqaution

so it look like 3x-(2x-1)=-1

do your combining of like terms and your division & you get x = -2

now plug x in to y=2x-1 to get y = -5